2020
DOI: 10.1103/physrevlett.124.038004
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependent Shear Response of Jammed Packings of Frictionless Spherical Particles

Abstract: The mechanical response of packings of purely repulsive, spherical particles to athermal, quasistatic simple shear near jamming onset is highly nonlinear. Previous studies have shown that, at small pressure p, the ensemble-averaged static shear modulus G − G0 scales with p α , where α ≈ 1, but above a characteristic pressure p * * , G − G0 ∼ p β , where β ≈ 0.5. However, we find that the shear modulus G i for an individual packing typically decreases linearly with p along a geometrical family where the contact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
5
34
0
Order By: Relevance
“…Several previous experimental studies of compressed emulsions [18,19] and packings of thin granular cylinders [20] have also found power-law scaling of the contact number and shear modulus with pressure during isotropic compression. In previous computational studies of packings of frictionless, spherical particles [21], we showed that there are two important contributions to the ensemble-averaged shear modulus: G f from geometrical families and G r from changes in the interparticle contact network during compression. For isotropic compression, jammed packings within a geometrical family are mechanically stable packings with different pressures that are related to each other by continuous, quasistatic changes in packing fraction with no changes in the interparticle contact network.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Several previous experimental studies of compressed emulsions [18,19] and packings of thin granular cylinders [20] have also found power-law scaling of the contact number and shear modulus with pressure during isotropic compression. In previous computational studies of packings of frictionless, spherical particles [21], we showed that there are two important contributions to the ensemble-averaged shear modulus: G f from geometrical families and G r from changes in the interparticle contact network during compression. For isotropic compression, jammed packings within a geometrical family are mechanically stable packings with different pressures that are related to each other by continuous, quasistatic changes in packing fraction with no changes in the interparticle contact network.…”
Section: Introductionmentioning
confidence: 87%
“…Numerous prior studies have shown that the ensembleaveraged shear modulus G for packings of frictionless, spherical particles increases as a power-law in pressure when P > P * * [12,17], where P * * ∼ N −2 decreases with increasing system size. For finite-sized systems, we have used the following scaling form for the ensemble-averaged shear modulus [21]:…”
Section: E Ensemble-averaged Shear Modulusmentioning
confidence: 99%
See 2 more Smart Citations
“…By means of smoothed interaction laws between bodies, simulations may reproduce some elasticity due to a virtual contact deflection, although the bodies themselves do not undergo strains. Using this approach, the elastic properties of particle assemblies have been studied, however restricting considerations of the small-strain domain of deformations [1][2][3][4]. More recently, the development of more advanced methods coupling discrete and finite elements [5][6][7][8][9][10] or meshless methods [11,12] have permitted to explore the compression behavior of soft granular media beyond jamming.…”
Section: Introductionmentioning
confidence: 99%